THE HUMAN RIGHT TO ADEQUATE FOOD, AGENDA 2030 AND SDGS: CHALLENGES AND PERSPECTIVES FOR ERADICATING HUNGER AND PROMOTING FOOD SECURITY IN BRAZIL (REMUNOM, 2026)
The Human Right to Adequate Food (HRtAF) was included by the UN in the 1948 Universal Declaration of Human Rights; subsequently, it was incorporated into the Brazilian legal system, according to Constitutional Amendment Proposal 064 of 2010, in which the Public Authorities assume the responsibility of guaranteeing this right to the Brazilian people. The objective of this work is to understand the human right to adequate food (HRtAF) in Brazil, contextualizing the HRtAF within the 2030 Agenda for Sustainable Development. This article was developed between September and October 2025, using the bibliographic method, through the collection, selection, and analysis of scientific articles related to the theme, as well as international documents and Brazilian legislation. The results demonstrated that, although there is instability in the programs and actions aimed at achieving the SDGs related to the HRtAF, since 2023 some public policies have been implemented or strengthened for this purpose, which led to Brazil being removed from the UN hunger map by 2025. It is concluded that, for the effective realization of the Right to Adequate Food, the public policies adopted must be multidimensional and overcome not only food insecurity and all forms of malnutrition, but also aim for advances in the social determinants and the effective elimination of social inequalities that result in improved quality of life for all.